2018
DOI: 10.1097/mao.0000000000001620
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Cochlear Implantation Outcomes Evaluated With General Health-related Patient-reported Outcome Measures

Abstract: Although regularly used, HRQOL measures are not intended to measure nor do they accurately reflect the complex difficulties facing CI patients. Only a medium positive effect of cochlear implantation on HRQOL was observed along with a low correlation between non-disease-specific PROMs and speech recognition. The use of such instruments in this population may underestimate the benefit of cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 38 publications
9
76
1
Order By: Relevance
“…Humes [2003] and Humes et al [2003] showed no correlation in a similar sample as well as in a large meta-analysis. In addition, absent to low correlations between patient self-report and speech recognition have been reported in cochlear implant users [Brendel et al, 2014;McRackan et al, 2016;Ramakers et al, 2017;McRackan et al, 2018a;McRackan et al, 2018b;Moberly et al, 2018]. Together, these data support the added value of PROMs as an independent measure of patient-perceived benefit from hearing interventions.…”
Section: Discussionmentioning
confidence: 74%
“…Humes [2003] and Humes et al [2003] showed no correlation in a similar sample as well as in a large meta-analysis. In addition, absent to low correlations between patient self-report and speech recognition have been reported in cochlear implant users [Brendel et al, 2014;McRackan et al, 2016;Ramakers et al, 2017;McRackan et al, 2018a;McRackan et al, 2018b;Moberly et al, 2018]. Together, these data support the added value of PROMs as an independent measure of patient-perceived benefit from hearing interventions.…”
Section: Discussionmentioning
confidence: 74%
“…To address the critical need for PROMs for adult CI users, we first developed the 81-item CIQOL item bank consisting of six domain-specific CIQOL item banks (McRackan, Bauschard, Hatch, Franko-Tobin, Droghini, Nguyen, et al, 2018) following the Patient-Reported Outcomes Measurement Information System (PROMIS) and Consensus-Based Standards for the Selection of Health Status Measurement Instruments (COSMIN) guidelines (Mokkink et al, 2010;PROMIS, 2013). To briefly summarize these steps, a systematic literature search was first conducted to identify PROMs previously used in the adult CI user population (McRackan, Bauschard, Hatch, Franko-Tobin, Droghini, Nguyen, et al, 2018;McRackan, Bauschard, Hatch, Franko-Tobin, Droghini, Velozo, et al, 2018). Information found through the literature search guided the development of a focus group protocol for patients with CI.…”
Section: Ciqol Item Bank Developmentmentioning
confidence: 99%
“…Although cochlear implantation is thought to provide benefits beyond communication, such as emotional state and social engagement, changes in speech recognition outcomes with cochlear implantation have been the primary research focus. Moreover, cochlear implant (CI) outcomes assessed using speech recognition (Adunka, Gantz, Dunn, Gurgel, & Buchman, 2018) correlate poorly with user self-reports of real-world communication ability and QOL (Capretta & Moberly, 2016;McRackan, Bauschard, Hatch, Franko-Tobin, Droghini, Nguyen, et al, 2018;McRackan, Bauschard, Hatch, Franko-Tobin, Droghini, Velozo, et al, 2018).…”
mentioning
confidence: 99%
“…Within the literature, cochlear implantation is frequently referred to as the "standard of care" [9,10], "treatment of choice" [11,12], or the "gold standard" for management of patients with severe-to-profound sensorineural hearing loss [13] perhaps based on the common belief that patients with severe-to-profound hearing loss cannot derive benefit from traditional hearing aids [c.f . 14].…”
Section: Introductionmentioning
confidence: 99%